Pemilihan Prioritas Berdasarkan Keinginan Konsumen Dengan Menggunakan Analytical Hierarchy Process Pada Travel PT X - N. E. Maitimu (ARIKA, 2010)
In this study discusses how to conduct a company policy on travel about assessment of consumer desire by using the method of Analytical Hierarchy Process (AHP). AHP is a method to obtain the best solution from several alternative solution by utilizing the comparison by pairs (pairwise comparison) as the basis in determining the choice of priorities. With the principle of decomposition then the whole issue will be split into elements of the simpler problems to become more structured. Then performed a comparative study that is the value of the relative importance of the two components at a certain rate elements associated with the level on the level above. The next step to determine the priority through pairwise comparison matrix, which can be determined value of eigen vector. With this method, the director or manager of the travel will be helpful in setting appropriate priorities for assessment or assessment results in accordance with the wishes of consumers.